Genital Abnormalities and Growth Retardation as Early Signs of Dilated Cardiomyopathy with Ataxia Syndrome - Kyriaki Papadopoulou-Legbelou; Maria Ntoumpara; Maria Kavga; Eleni P. Kotanidou; Ioannis Papoulidis; Assimina Galli-Tsinopoulou; Maria Fotoulaki (Case Reports in Genetics)
Dilated cardiomyopathy with ataxia syndrome is a rare mitochondrial disease caused by autosomal recessive mutations in the DNAJC19 gene. The disease has been described in detail in the Canadian Hutterite population, but a few sporadic cases with de novo mutations have been published worldwide. We describe a homozygous pathogenic variant in the DNAJC19 gene, diagnosed in Northern Greece, presenting with genital anomalies, growth failure, cardiomyopathy, and ataxia, but without increased urinary 3-methylglutaconic acid and additional presence of vitamin D disorders, hypercalciuria, and osteopenia. This case not only expands the clinical characteristics of 3-methylglutaconic aciduria type V (MGCA5) but also highlights the power of genetic analysis for detecting a diagnosis when the metabolic screen is negative.